Implementasi Manajemen Kurikulum Integratif di Sekolah Dasar - Nur Shinta Fillaili; Sugiyar (Excelencia: Journal of Islamic Education & Management, 2024)
Thanks to the integrative curriculum management at SDIT Al Ikhlas Mantren, the school can adapt to the ever-changing demands of the current world, characterized by pressure and globalization. By introducing an innovative and relevant curriculum, SDIT Al Ikhlas Mantren can prepare students with competent skills to face future challenges. The purpose of this research is to understand the management of change in the implementation of the Integrated Curriculum at SDIT Al Ikhlas Mantren, with a focus on three main aspects: 1) the implementation of the Integrated Curriculum in the school, 2) the influence of integrated management, 3) factors that support and hinder the process of the Integrated Curriculum. This study employs a qualitative approach and field research based at SDIT Al Ikhlas Mantren Karangrejo Magetan. Data collection is carried out through participant observation, in-depth interviews, and documentation. Data analysis uses data reduction techniques, data presentation, followed by drawing conclusions and verification. Through the data collection process, this research concludes that the implementation of the Integrated Curriculum Management at SDIT Al Ikhlas Mantren involves three management functions. 1) The implementation of curriculum integration is carried out by integrating the curriculum implementation program and integrating government curriculum implementation. The evaluation of curriculum integration is performed by evaluating the curriculum, including context evaluation, input evaluation, process evaluation, and product evaluation. 2) School curriculum integration obstacles use a convergence program oriented towards learning about the attributes of Allah's names for coloring, the school's success in achieving its goals, teachers feeling the benefits of the curriculum for students, and parents feeling alignment with the school's vision and mission, and a positive impact on the students. 3) Curriculum integration planning is carried out by integrating curriculum objectives and integrating curriculum content organization with the fragmented integration model of the government.